Intelligent and Efficient Electrical Systems Selected Proceedings of ICIEES'17 (Lecture Notes in Electrical Engineering,, 2018)
This book presents selected papers from International Conference on Intelligent and Efficient Electrical Systems (ICIEES'17). The volume brings together content from both industry and academia. The book focuses on energy efficiency in electrical systems and covers en trende topics such as control of renewable energy systems. The collaborative industry-academia perspective of the conference ensures that equal emphasis is laid on novel topics and practical applications. The contents of this volume will prove useful to researchers and practicing engineers alike.